2021
DOI: 10.3390/mi13010041
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning Based Estimation of Dielectrophoretic Force

Abstract: The ability to accurately quantify dielectrophoretic (DEP) force is critical in the development of high-efficiency microfluidic systems. This is the first reported work that combines a textile electrode-based DEP sensing system with deep learning in order to estimate the DEP forces invoked on microparticles. We demonstrate how our deep learning model can process micrographs of pearl chains of polystyrene (PS) microbeads to estimate the DEP forces experienced. Numerous images obtained from our experiments at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In 16 negative DEP of the PS beads was observed when a voltage of 3.8 V pp of 480 kHz frequency was applied, forming 6–7 beads-long pearl chain. Similar studies on yeast cells have been reported when voltage (3.7 V pp ) at a field frequency of 580 kHz exhibited positive DEP, the number of particles aggregated were found to be related to the applied voltage 16 , 17 .…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…In 16 negative DEP of the PS beads was observed when a voltage of 3.8 V pp of 480 kHz frequency was applied, forming 6–7 beads-long pearl chain. Similar studies on yeast cells have been reported when voltage (3.7 V pp ) at a field frequency of 580 kHz exhibited positive DEP, the number of particles aggregated were found to be related to the applied voltage 16 , 17 .…”
Section: Introductionsupporting
confidence: 82%
“…The interaction of a non-uniform electric field with a dipole is known as dielectrophoretic force .To improve the approximation of the exerted on the particles in terms of the voltage applied, a more tangible and straightforward model is required to advance DEP aided sensing systems. The when the particle is significantly smaller than the non-uniformities in the electric field is given in 17 as: where is the radius of spherical microparticles in a medium, under an alternating current (AC) field ; depends on the product of the localized field with its gradient ( ) and the frequency-dependent complex dielectric contrast of the particle versus the medium, as given by real-part of the Clausius–Mossoti factor ; …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations